Comparative Analysis of Horizontal Axis Wind Turbine Rotors with and without winglet at various wind speeds using Computational Fluid Dynamics Approach - Chhetri, Ashim; Pandey, Aayus; Lamsal, Gaurav; Dharel, Bijaya; Subedi, Nishan; Awasthi, Pawan C.; Karki, Dipesh (Journal of Engineering and Sciences, 2025)
This project investigates the aerodynamic performance of a Horizontal Axis Wind Turbine (HAWT) blade using NREL S-series airfoils (S830, S831, S832) with and without a winglet at various wind speeds. The blade was designed in QBlade and modeled in SolidWorks, with simulations performed in ANSYS Fluent using a steady-state RANS approach and the SST k–ω turbulence model. A winglet was added to the blade tip to assess its effect on performance. The computational domain applied the Multiple Reference Frame (MRF) to simulate rotating effects. Results show that the winglet improves power output by up to 3.55% at low wind speeds, with smaller gains at higher speeds. Comparative torque analyses and mesh-independence tests were performed to validate numerical accuracy. This suggests that winglets help reduce energy losses and improve turbine performance, especially at lower wind speeds.